Transaksi Kemitraan Usaha antara Rumah Sakit Umum DR. H. Koesnadi dengan Layanan Kesehatan BPJS Perspektif Hukum Ekonomi Syari`ah - Hilmi Ridho (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2022)
This study determines the form of cooperation transactions between BPJS Kesehatan and RSU Dr H. Koesnadi and finds out the views of Islamic law related to service transactions and buying and selling of facilities.The research method used was descriptive prescriptive, and data collection techniques were observation, interviews, documentation, and data analysis techniques, namely editing and organizing, and checking the validity of the data.Conclusion of the RSU Partnership discussion. Dr H. Koesnadi Bondowoso with BPJS Health in the field of health services had been going well. The form of cooperation between two or more people who were entitled to provide services to the community or syirkah engaged in the service sector. Imam Shafi`i believed that this work syirkah was not valid. But other imams allow and legal. Provision of services as provided by the RSU. Dr H. Koesnadi Bondowoso in the form of inpatient services, outpatient services, and other services, were rental services including rental contracts and the law was permissible, which in Islamic economic terms was called an ijarah contract. While the provision of consumables such as medicines, infusions, blood transfusions and so on, includes buying and selling transactions and this was allowed according to Islamic law.